Karl Marx and the Intellectual Origins of Dialectical Materialism - White, J. author. aut Link
XI, 416 p.
Keywords: The book provides a genealogy of 'dialectical materialism' by tracing the development of Marxist ideas from their origins in German philosophical thought to the ideology of the social-democratic groups in Russia in the 1890s, from which Lenin and the revolutionary generation emerged. It reconstructs Marx's original conceptions and examines the modifications that were made to them by himself and by his Russian followers, which eventually gave rise to the doctrine of 'dialectical materialism', first expounded by Plekhanov.